High-performance near-infrared photodetector based on nano-layered MoSe2. (22nd May 2017) - Ko, Pil Ju; Abderrahmane, Abdelkader; Kim, Nam–Hoon; Sandhu, Adarsh
Abstract: In recent years, the integration of two-dimensional (2D) nanomaterials, especially transition metal chalcogendies (TMCs) and dichalcogendies (TMDCs), into electronic devices have been extensively studied owing to their exceptional physical properties such as high transparency, strong photoluminescence, and tunable bandgap depending on the number of layers. Herein, we report the optoelectronic properties of few-layered MoSe2 -based back-gated phototransistors used for photodetection. The photoresponsivity could be easily controlled to reach a maximum value of 238 AW −1 under near-infrared light excitation, achieving a high specific detectivity ( D * = 7.6 × 10 11 cm Hz 1/2 W − 1 ) . Few-layered MoSe2 exhibited excellent optoelectronic properties compared with those reported previously for multilayered 2D material-based photodetectors, indicating that our device is one of the best high-performance nanoscale near-infrared photodetectors based on multilayered two-dimensional materials.